US politics and climate change : science confronts policy - Sussman, Glen (Lynne Rienner Publishers, 2013)
Why is climate change the subject of such vehement political rhetoric in the United States? What explains the policy deadlock that has existed for nearly two decades-and that has resulted in the failure of US leadership in the international arena? Addressing these questions, Glen Sussman and Byron Daynes trace the evolution of US climate change policy, assess how key players-the scientific community, Congress, the president, the judiciary, interest groups, the states, and the public-have responded to climate change, and explore the prospects for effective policymaking in the future.